2023
DOI: 10.3390/ijms24043829
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin-3-O-glucoside Contributes to Leaf Color Change by Regulating Two bHLH Transcription Factors in Phoebe bournei

Abstract: Anthocyanins produce different-colored pigments in plant organs, which provide ornamental value. Thus, this study was conducted to understand the mechanism of anthocyanin synthesis in ornamental plants. Phoebe bournei, a Chinese specialty tree, has high ornamental and economic value due to its rich leaf color and diverse metabolic products. Here, the metabolic data and gene expression of red P. bournei leaves at the three developmental stages were evaluated to elucidate the color-production mechanism in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…In particular, the glycosylation and acylation products of pelargonidin and cyanidin had high content. Previous studies have shown that pelargonidin 3-O-glucoside and cyanidin 3-O-glucoside and their modified products are important for the purplish-red or red color [ 33 , 34 ]. Although peonidin and delphinidin also had some effect on flower color, there was no significant difference between the two substances in the three cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the glycosylation and acylation products of pelargonidin and cyanidin had high content. Previous studies have shown that pelargonidin 3-O-glucoside and cyanidin 3-O-glucoside and their modified products are important for the purplish-red or red color [ 33 , 34 ]. Although peonidin and delphinidin also had some effect on flower color, there was no significant difference between the two substances in the three cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…In acer tri orum, cyanidin-3-O-arabinoside is closely related to red leaf colour [36]. The major anthocyanin in the leaves of Phoebe bournei is cyanidin-3-O-glucoside [27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, cyanidin-3,5-O-diglucoside is the major anthocyanin for the production of red leaves in Acer pseudosieboldianum, and PAL, ANS, DFR, and F3'H are structural genes involved in leaf colour production [26]. In a study on Phoebe bournei [27], cyanidin-3-O-glucoside was suggested to be a metabolite associated with red leaf colouration, and avanone 3'-hydroxy-lase (PbF3'H) was signi cantly associated with cyanidin-3-O-glucoside.…”
mentioning
confidence: 99%
“…acephala de Candolle), the white color of the inner leaves is attributed to an extremely low or absent level of anthocyanin biosynthesis, coupled with high chlorophyll degradation and minimal chlorophyll biosynthesis [ 6 ]. In Phoebe bournei , Wang et al [ 7 ] discovered that the anthocyanin content gradually decreased as the leaves developed. They suggested that the anthocyanin cyanidin-3- O -glucoside and the PbF3′H , PbbHLH1 , and PbbHLH2 genes are likely to be responsible for the red leaf color.…”
Section: Introductionmentioning
confidence: 99%